Survey of Routing Protocols under Realistic Mobility and Traffic (International Journal of Engineering and Computer Science, 2018)
Mobile ad hoc networks are a dynamic and unpredictable community topology. There are numerous routing protocols that have been proposed for MANETs. Maximum pervious research centered on improving the present routing protocols or designing new routing algorithms. In our work, we investigated and compared the effect of mobility models on routing protocols for various site visitors instructions in MANETs. There have been many factors that affected the overall performance of routing protocols which include mobility and visitors styles. We designed several simulation models that added these factors together and measured the software performance in terms of end -to-end throughput (bit rate), latency, and jitter. three instructions of MANET routing algorithms (Proactive, Reactive, and Hybrid),  mobility models (Random Waypoint and group), and three instructions of visitors styles (constant bit rate, variable bit rate, and random) have been used.